MAGNITUDE OF SOIL SALINITY HAZARD IN DAUSA FADAMA, DIGOL VILLAGE, DANBATTA LOCAL GOVERNMENT AREA OF KANO STATE (FUDMA JOURNAL OF SCIENCES, 2023)
Soil salinization and sodication are identified as one of the major processes leading to land degradation and loss of fertile agricultural lands worldwide. The magnitude or level of soil salinity in the study area was computed using EC values recorded in ds/m. These values were used to classify the soil into differentclasses based on the extent or severity of their salinity. It was found that more than 90 percent of the soils of the fadama fall within the EC classes that ranges from very low salinity class to low salinity class. This shows that the structure of the soils of the fadama is having larger silt and sand particles because its ECreadings are generally lower. This is because fine textured soils are generally more prone to salinization compared with coarse-textured soils. The area classified as very high salinity is situated within the lowest point of the fadama. Deep tillage can be applied in order to improve drainage by breaking up the compactedsoil surface and hard pans which restrict downward flow of water. Application of crop residues will lead to decreases of salt accumulation since there will be less evaporation from such residue covered surfaces. Such surfaces would have high soil moisture content that can keep the soil less saline. Cultivation of cropswith long tap roots etc. are all recommended for combating soil salinity in the study area.
Keywords: Electrical Conductivity, Soil Fertility, Halophytes, Crop Residues, Deep tillage